2021
DOI: 10.1161/circresaha.121.319517
|View full text |Cite
|
Sign up to set email alerts
|

Novel Paracrine Action of Endothelium Enhances Glucose Uptake in Muscle and Fat

Abstract: Rationale: A hallmark of type 2 diabetes is insulin resistance, which leads to increased endothelial cell (EC) production of superoxide and a simultaneous reduction in the availability of the vasoprotective signaling radical NO. We recently demonstrated in preclinical models that type 2 diabetes simultaneously causes resistance to IGF-1 (insulin-like growth factor-1)–mediated glucose lowering and endothelial NO release. Objective: To examine the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
7
2
Order By: Relevance
“…Among various regulatory factors reviewed here, NO, PGI 2 , PGE 2 , PDGF-CC, and the yet-to-be-identified PPARγ-activating lipid, share great therapeutic potential to upregulate energy expenditure by increasing adipocyte beiging, enhancing AT insulin sensitivity, and alleviating undesirable AT inflammation. Our recent report also suggested that endothelial-derived ROS plays a role in enhancing whole-body (including BAT) insulin sensitivity in response to short-term overnutrition ( 167 ). However, diseased upregulation of endothelial-derived ET-1, ROS, heparanse and pro-inflammatory mediators can bring detrimental metabolic and inflammatory outcomes by upregulating lipolysis and inducing insulin resistance.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Among various regulatory factors reviewed here, NO, PGI 2 , PGE 2 , PDGF-CC, and the yet-to-be-identified PPARγ-activating lipid, share great therapeutic potential to upregulate energy expenditure by increasing adipocyte beiging, enhancing AT insulin sensitivity, and alleviating undesirable AT inflammation. Our recent report also suggested that endothelial-derived ROS plays a role in enhancing whole-body (including BAT) insulin sensitivity in response to short-term overnutrition ( 167 ). However, diseased upregulation of endothelial-derived ET-1, ROS, heparanse and pro-inflammatory mediators can bring detrimental metabolic and inflammatory outcomes by upregulating lipolysis and inducing insulin resistance.…”
Section: Discussionmentioning
confidence: 95%
“…In patients with obesity, higher levels of H 2 O 2 were determined in visceral AT and were suggested to correlate with insulin resistance ( 165 ) as a result of upregulated endothelial release of H 2 O 2 . In diet-induced obese mice, endothelial extracellular H 2 O 2 production is upregulated ( 166 ), predominantly by NOX4, and is suggested to mediate glucose disposal in BAT ( 167 ). We recently reported that endothelial insulin and IGF-1 signaling governs endothelial production of miR-25 which suppresses NOX4 expression ( 167 ).…”
Section: Small Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nox4 activity has also been shown to be increased in the serum of patients with type 2 diabetes mellitus [ 141 ]. More recently, however, in a unique murine model of EC insulin resistance with whole body insulin sensitivity, we demonstrated reduced EC expression of Nox2 and miR-25, but increased expression of Nox4 and an associated increased production of H 2 O 2 [ 142 ]. Furthermore, transgenic mice with endothelial targeted overexpression of NOX4 had increased H 2 O 2 production and H 2 O 2 -induced hyperpolarization (without affecting endothelial NO bioactivity) within their coronary microvascular ECs, resulting in significantly greater acetylcholine- or histamine-induced vasodilatation compared to their wild type littermates [ 143 ].…”
Section: Nox4 and Endothelial Functionmentioning
confidence: 99%